2014
DOI: 10.1590/0074-0276140304
|View full text |Cite
|
Sign up to set email alerts
|

Updating the geographical distribution and frequency of Aedes albopictus in Brazil with remarks regarding its range in the Americas

Abstract: The geographical distribution of Aedes albopictus in Brazil was updated according to the data recorded across the country over the last eight years. Countrywide house indexes (HI) for Ae. albopictus in urban and suburban areas were described for the first time using a sample of Brazilian municipalities. This mosquito is currently present in at least 59% of the Brazilian municipalities and in 24 of the 27 federal units (i.e., 26 states and the Federal District). In 34 Brazilian municipalities, the HI values for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
12

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 49 publications
2
95
0
12
Order By: Relevance
“…aegypti is dispersed in Brazil, especially in the northern, northeastern, and central eastern regions (191,192), but populations of Ae. albopictus are larger in subtropical areas, especially in southern Brazil (193). It was first suggested that ZIKV was introduced to Brazil during the World Cup soccer competition in 2014 (28,172,194), but teams from Pacific countries with ongoing circulation of ZIKV did not participate in that competition.…”
Section: Emergence Of Zikv In the Americasmentioning
confidence: 99%
“…aegypti is dispersed in Brazil, especially in the northern, northeastern, and central eastern regions (191,192), but populations of Ae. albopictus are larger in subtropical areas, especially in southern Brazil (193). It was first suggested that ZIKV was introduced to Brazil during the World Cup soccer competition in 2014 (28,172,194), but teams from Pacific countries with ongoing circulation of ZIKV did not participate in that competition.…”
Section: Emergence Of Zikv In the Americasmentioning
confidence: 99%
“…In Brazil, Ae. albopictus was present in 59% of municipalities in 2014 (58) and in 24 of 27 states (59) . It is adapted to both urban and sylvatic habitats, including bromeliads (60) , tree holes (also with Ae.…”
Section: Vectorial Role Of Aedes (Stegomyia) Mosquitoesmentioning
confidence: 99%
“…albopictus has been detected in different Brazilian regions (Carvalho et al, 2014). As a result of industrial expansion, Ae.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus in Brazil at the municipal level with the mosquito being detected in more than half of all Brazilian municipalities (59.0%) (Carvalho et al, 2014). The highest reported HI (house index) values are in municipalities and states located in the southeast (Carvalho et al, 2014). Its presence and broad distribution in Brazilian dengue endemic cities has never been correlated with epidemics.…”
Section: Introductionmentioning
confidence: 99%